Prediction by a Genetic Algorithm of the Fiber-Matrix Interface Damage for Composite Material. Part 1. Study of Shear Damage in Two Composites T300/914 and PEEK/APC2 - Mokaddem, A.; Alami, M.; Doumi, B.; Boutaoush, A. (Проблемы прочности, 2014)
We have conducted research on the effect of fiber arrangement on the optimization of the damage to the interface, recently published. We develop in this paper the evolution of the damage in the shearing direction by genetic algorithm. The results obtained by varying the shear rate of the interface of the two materials studied T300 and PEEK, show a good agreement between our genetic approach and the mathematical models presented by Cox and Weibull.